Positive electrode material, preparation method thereof and battery
By controlling the content and particle size distribution of free nitrate in the positive electrode material, and using nitric acid annealing and sintering treatment, the structural stability and cyclic performance of the positive electrode material at high voltage is solved, and higher high voltage resistance and cyclic stability are achieved.
Patent Information
- Application Number
- CN202411976483.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-04
AI Technical Summary
Existing positive electrode materials are prone to excessive lithium ions disengagement, mixed cation discharge, and lattice oxygen disengagement under high voltage, resulting in reduced capacity and circulation performance and poor structural stability, affecting the safety and high-performance use of the battery.
By controlling the mass content of free nitrate in the positive electrode material between 10 ppm and 100 ppm, and adjusting the proportion of particles with a particle size less than 1 μm to between 8% and 16%, the positive electrode material is prepared by nitric acid annealing and sintering treatment to improve its particle stacking density and lithium ion transport efficiency.
It improves the high voltage resistance of the positive electrode material, reduces crystal structure distortion, improves structural stability and cycling performance, enhances lithium ion transmission efficiency, and extends the cycle life of the battery.
Smart Images

Figure CN119764413A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of positive electrode materials, and in particular relates to positive electrode materials and preparation methods thereof, and batteries. Background Art
[0002] Lithium-ion batteries are widely used in laptops, mobile phones, digital products and other fields due to their high energy density, good safety performance, long cycle life and environmental friendliness. The development of positive electrode materials is relatively slow compared to the development of large-capacity negative electrode materials (about 800-1000mAh / g). Therefore, researchers currently focus on developing large-capacity and high-voltage positive electrode materials to improve the energy density of lithium-ion batteries.
[0003] As the nickel content in the positive electrode material increases, it will inevitably cause problems such as lithium-nickel mixing, structural degradation, reduced thermal stability and increased residual alkali, which will lead to battery capacity degradation, reduced cycle and poor structural stability, affecting its safe and high-performance use. Moreover, under high voltage, due to the excessive release of lithium ions in the positive electrode material, cation mixing will occur, which will in turn cause the release of lattice oxygen. While the battery produces gas, it will also cause a significant decrease in the capacity and cycle performance of the positive electrode material. In addition, the side reaction of the positive electrode material with the electrolyte at high potential is intensified, producing carbon dioxide gas, which changes the surface crystal structure of the positive electrode material and causes the loss of lithium storage sites.
[0004] Therefore, how to improve the high voltage resistance of the positive electrode material and reduce the crystal structure distortion of the positive electrode material is one of the problems that need to be solved urgently. Summary of the invention
[0005] The present application provides a positive electrode material and a preparation method thereof, and a battery. The positive electrode material of the present application has excellent high voltage resistance, can reduce the crystal structure distortion of the positive electrode material, and thus improve the structural stability and cycle performance of the positive electrode material.
[0006] In a first aspect, the present application provides a positive electrode material, wherein the mass content of free nitrate ions in the positive electrode material is Qppm, 10≤Q≤100; and the number of particles with a particle size less than 1 μm in the positive electrode material accounts for R%, 8≤R≤16.
[0007] In some embodiments, the volume particle size distribution of the positive electrode material satisfies: 0.2 μm≤D10≤2.0 μm, 2.0 μm≤D50≤5.0 μm, 6.0 μm≤D90≤12.0 μm.
[0008] In some embodiments, the volume particle size distribution of the positive electrode material satisfies: 0.8≤(D90-D10) / D50≤2.0.
[0009] In some embodiments, the mass content of free sulfate in the positive electrode material is K ppm, 10≤K≤800.
[0010] In some embodiments, the positive electrode material is a single crystal material, the positive electrode material includes grains with the same orientation, and the grain size of the grains is 1 μm to 5 μm.
[0011] In some embodiments, the chemical formula of the positive electrode material is Li n Ni x Co y N z M s O2, wherein 0.9≤n≤1.1, 0<x<1, 0<y<1, 0<z<1, 0≤s<1, x+y+z+s=1, N includes at least one of Mn and Al, and M includes at least one of Zr, Mg, W, Mo, Ti, Ba, Sr, Cr, Zn, Y, V, Cu, B, and Nb.
[0012] In some embodiments, during the first cycle of charge and discharge, the structural recovery degree δ of the positive electrode material satisfies: 99.7%≤δ≤100.0%; wherein δ=θ1 / θ2*100%, θ1 is the diffraction angle of the positive electrode material at the (003) crystal plane diffraction peak measured by X-ray diffraction at the beginning of the first cycle of charging, and θ2 is the diffraction angle of the positive electrode material at the (003) crystal plane diffraction peak measured by X-ray diffraction at the end of the first cycle of discharge.
[0013] In some embodiments, the specific surface area of the positive electrode material is 0.5 m 2 / g~1.5m 2 / g.
[0014] In some embodiments, the tap density of the positive electrode material is 1.0 g / cm 3 ~3.0g / cm 3 .
[0015] In some embodiments, the compaction density of the positive electrode material is 2.5 g / cm 3 ~3.5g / cm 3 .
[0016] In some embodiments, the bulk density of the positive electrode material is 0.5 g / cm 3 ~1.5g / cm 3 .
[0017] In a second aspect, the present application provides a method for preparing a positive electrode material, comprising the following steps:
[0018] The hydroxide precursor of the positive electrode material is subjected to nitration annealing treatment, which refers to annealing treatment carried out in a nitric acid atmosphere for a certain period of time to obtain an oxide precursor containing nitrate ions;
[0019] A mixture of an oxide precursor containing nitrate ions and a lithium source is subjected to a sintering treatment, and the sintering product is crushed to obtain a positive electrode material, wherein the mass content of free nitrate in the positive electrode material is Q ppm, 10≤Q≤100; the number of particles with a particle size less than 1 μm in the positive electrode material accounts for R%, 8≤R≤16.
[0020] In a third aspect, the present application provides a battery, comprising a positive electrode material or a positive electrode material prepared by the above-mentioned method for preparing the positive electrode material.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] The present application controls the mass content of free nitrate in the positive electrode material to be between 10ppm and 100ppm, and controls the number of particles with a particle size of less than 1μm in the positive electrode material to be between 8% and 16%. An appropriate amount of small particles can improve the stacking density between the positive electrode material particles without causing too many side reactions, improve the transmission of lithium ions, reduce the internal resistance of the positive electrode material, reduce the lithium ion transmission barrier, and improve the lithium deintercalation efficiency of the positive electrode material. Under the synergistic effect of an appropriate amount of free nitrate and particles with a particle size of less than 1μm, the high voltage resistance and high capacity of the positive electrode material can be improved, while the lithium ion transmission efficiency of the positive electrode material can be improved, and the cycle stability of the positive electrode material can be improved.
[0023] The preparation method of the positive electrode material provided by the present application comprises the following steps: subjecting the hydroxide precursor of the positive electrode material to nitration annealing treatment to obtain an oxide precursor containing nitrate ions; subjecting the mixture of the oxide precursor containing nitrate ions and a lithium source to a sintering treatment, wherein the reaction activity of the oxide precursor during the sintering process is lower than that of the hydroxide precursor, which is conducive to the uniform growth of the primary particles, the increase in the particle size of the primary particles, and the decrease in the number of particles with a particle size of less than 1 μm. The mass content of free nitrate in the positive electrode material prepared by the present application is between 10ppm and 100ppm, and the number of particles with a particle size of less than 1 μm in the positive electrode material is controlled to account for between 8% and 16%. An appropriate amount of small particles can improve the stacking compactness between the particles of the positive electrode material without causing excessive side reactions, improve the transmission of lithium ions, reduce the internal resistance of the positive electrode material, reduce the lithium ion transmission barrier, and improve the lithium deintercalation efficiency of the positive electrode material. With the synergistic effect of an appropriate amount of free nitrate ions and particles with a particle size of less than 1 μm, the high voltage resistance and high capacity of the positive electrode material can be improved, while the lithium ion transmission efficiency of the positive electrode material can be enhanced and the cycle stability of the positive electrode material can be improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the embodiments of the present application or the technical solutions of the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.
[0025] Figure 1 A schematic diagram of the discharge state of a battery provided in an embodiment of the present application.
[0026] Figure 2 This is the Li element spectrum obtained by XPS characterization of the positive electrode material prepared in Example 1 of the present application after the first charge and discharge.
[0027] Figure 3 This is the Li element spectrum obtained by XPS characterization of the positive electrode material prepared in Comparative Example 1 of the present application after the first charge and discharge. DETAILED DESCRIPTION
[0028] In order to better understand the technical solution of the present application, the embodiments of the present application are described in detail below with reference to the accompanying drawings.
[0029] It should be clear that the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.
[0030] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features.
[0031] In order to easily understand the present invention, specific terms are appropriately defined in this application. Unless otherwise defined herein, scientific terms and technical terms used in the present invention have the meanings commonly understood by those skilled in the art to which the present invention belongs.
[0032] As used herein, the term "primary particles" refers to particles that exist individually without forming agglomerates.
[0033] The present application provides a positive electrode material, wherein the mass content of free nitrate in the positive electrode material is Q ppm, 10≤Q≤100; and the number of particles with a particle size less than 1 μm in the positive electrode material accounts for R%, 8≤R≤16.
[0034] The mass content of free nitrate in the positive electrode material provided in the present application is Q ppm, 10≤Q≤100; the mass content Q of free nitrate in the positive electrode material satisfies the above range, and the positive electrode material has good structural stability and cycle performance. The inventor speculates that this is because the free nitrate in the positive electrode material can react with active lithium ions during the charge and discharge cycle, thereby inducing the formation of Li2O on the surface of the positive electrode material. Li2O has high voltage resistance, which helps to improve the high voltage resistance of the positive electrode material and reduce the occurrence of side reactions between the positive electrode material and the electrolyte. In addition, Li2O is distributed on the surface of the positive electrode material, which can reduce the surface defects of the positive electrode material, reduce the surface energy of the positive electrode material, help to improve the crystal structure stability of the positive electrode material, reduce oxygen escape in the lattice, and thus reduce the crystal structure distortion of the positive electrode material.
[0035] However, since Li2O on the surface of the positive electrode material will affect ion transmission, the kinetics of lithium deintercalation reaction of the positive electrode material will decrease. Therefore, the present application controls the mass content of free nitrate ions in the positive electrode material to be between 10ppm and 100ppm, and at the same time controls the number of particles with a particle size of less than 1μm in the positive electrode material to be between 8% and 16%. An appropriate amount of small particles can improve the stacking compactness between the positive electrode material particles without causing too many side reactions, which can improve the transmission of lithium ions, reduce the internal resistance of the positive electrode material, reduce the lithium ion transmission barrier, and improve the lithium deintercalation efficiency of the positive electrode material. Under the synergistic effect of an appropriate amount of free nitrate ions and particles with a particle size of less than 1μm, the high voltage resistance and high capacity of the positive electrode material can be improved, while the lithium ion transmission efficiency of the positive electrode material can be improved, and the cycle stability of the positive electrode material can be improved.
[0036] In some embodiments, the mass content of the free nitrate of the positive electrode material can specifically be 10ppm, 12ppm, 25ppm, 30ppm, 50ppm, 68ppm, 75ppm, 80ppm, 85ppm, 95ppm or 100ppm, etc., and of course, it can also be other values within the above range, which are not limited here. The mass content of the free nitrate of the positive electrode material is too high, which will cause too much Li2O to be formed on the surface of the positive electrode material, so that the ion transmission of the positive electrode material is blocked. When the mass content of the free nitrate of the positive electrode material is too low, during the charge and discharge process, the amount of Li2O formed on the surface of the positive electrode material is too little, and the side reaction of the positive electrode material and the electrolyte is aggravated, especially under high voltage charge and discharge state, the capacity loss of the positive electrode material is aggravated. The present application controls the mass content of free nitrate ions in the positive electrode material within the above range, and can induce the formation of an appropriate amount of Li2O on the surface of the positive electrode material particles after cyclic charge and discharge. The appropriate amount of Li2O can reduce the surface defects of the positive electrode material, reduce the surface energy of the positive electrode material, help to improve the crystal structure stability of the positive electrode material, and help the positive electrode material to have both high voltage resistance and excellent cycle stability.
[0037] It should be noted that after the first charge and discharge of the battery formed by the positive electrode material, the nitrate ions on the surface of the positive electrode material can react: 2Li + +NO3 - +2e - =Li2O+NO 2- , inducing the formation of a certain amount of Li2O protective layer on the surface of the positive electrode material. This protective layer has high chemical stability, can remain inert under high voltage, effectively isolate the electrolyte, and reduce the occurrence of side reactions.
[0038] In some embodiments, the number of particles with a particle size of less than 1 μm in the positive electrode material accounts for 8% to 16%, which can be 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15% or 16%, 9%, etc., and of course, it can also be other values within the above range, which are not limited here. When the number of particles with a particle size of less than 1 μm accounts for too much, it means that the number of micropowders increases, the particle size distribution width of the positive electrode material increases, and the compaction density of the positive electrode material can be improved, but the specific surface area of the positive electrode material increases, and the smaller the particle size, the more serious the side reaction with the electrolyte. In addition, these micropowders are easy to complicate the lithium ion transmission path during the charge and discharge cycle, affecting the deintercalation of lithium ions, and reducing the structural stability and cycle stability of the positive electrode material. When the number of particles with a particle size of less than 1 μm accounts for too little, the transmission path of lithium ions increases, the initial DCR of the positive electrode material increases, and the compaction density of the positive electrode material decreases. The present application controls the proportion of particles with a particle size less than 1 μm within the above range, which can shorten the lithium ion diffusion path, reduce the transmission barrier between the positive electrode material particles, ensure that the compaction density of the positive electrode material is within an appropriate range, and improve the energy density of the positive electrode material. At the same time, it is beneficial to reduce the occurrence of side reactions between the positive electrode material and the electrolyte, reduce impedance, and improve the capacity and cycle stability of the positive electrode material.
[0039] In some embodiments, the positive electrode material has the general chemical formula Li n Ni x Co y N z M s O2, wherein 0.9≤n≤1.1, 0<x<1, 0<y<1, 0<z<1, 0≤s<1, x+y+z+s=1, N includes at least one of Mn and Al, and M includes at least one of Zr, Mg, W, Mo, Ti, Ba, Sr, Cr, Zn, Y, V, Cu, B, and Nb.
[0040] Specifically, the value of n can be 0.90, 0.92, 0.95, 0.96, 0.98, 0.99, 1.0, 1.02, 1.05, 1.08 or 1.1, etc., the value range of x can be 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 0.92, etc., and the value range of y can be 0.001, 0.06, 0.1, 0.2, 0.28, 0.3, 0.4, 0.5, 0. 6, 0.7, 0.8, 0.9 or 0.92, etc., the value range of z can be 0.001, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 0.92, etc., the value range of s can be 0, 0.001, 0.005, 0.008, 0.01, 0.02, 0.05, 0.08, 0.1, 0.2, 0.3 or 0.5, etc., of course, it can also be other values within the above range, which is not limited here.
[0041] The positive electrode material is a nickel-cobalt-lithium composite oxide, and the nickel-cobalt-lithium composite oxide includes a nickel-cobalt-manganese-lithium composite oxide or a nickel-cobalt-aluminum-lithium composite oxide.
[0042] In some embodiments, the volume particle size distribution of the positive electrode material satisfies: 0.2 μm≤D10≤2.0 μm, 2.0 μm≤D50≤5.0 μm, 6.0 μm≤D90≤12.0 μm. Specifically, D10 can be 0.2μm, 0.3μm, 0.5μm, 0.8μm, 1.0μm, 1.2μm, 1.4μm, 1.5μm, 1.8μm or 2.0μm, etc., D50 can be 2.0μm, 2.3μm, 2.5μm, 2.8μm, 3.0μm, 3.2μm, 3.5μm, 3.8μm, 4.0μm, 4.2μm, 4.5μm or 5.0μm, etc., D90 can be 6.0μm, 6.5μm, 6.8μm, 7.0μm, 8.0μm, 9.2μm, 10.5μm, 11μm, 11.5μm, 11.8μm or 12.0μm, etc., and of course it can also be other values within the above range, which are not limited here. In the present application, controlling the volume particle size distribution of the positive electrode material to meet the above conditions can improve the compaction density of the positive electrode material and enhance the cycle stability of the positive electrode material.
[0043] In some embodiments, the volume particle size distribution width of the positive electrode material satisfies: 0.8≤(D90-D10) / D50≤2.0, which can be 0.8, 0.9, 1.0, 1.09, 1.1, 1.2, 1.25, 1.3, 1.35, 1.4, 1.45, 1.5, 1.6, 1.7, 1.8 or 2.0, etc., and of course, it can also be other values within the above range, which is not limited here. The present application can improve the compaction density of the positive electrode material and the energy density of the battery made of the positive electrode material by controlling the particle size distribution width of the positive electrode material within the above range.
[0044] In some embodiments, the mass content of free sulfate of the positive electrode material is K ppm, 10≤K≤800, specifically 10ppm, 50ppm, 80ppm, 100ppm, 150ppm, 200ppm, 275ppm, 400ppm, 470ppm, 560ppm, 650ppm, 780ppm or 800ppm, etc., and of course, other values within the above range may be used, which are not limited here. In the present application, controlling the mass content of free sulfate within the above range can increase the migration rate of lithium ions, increase the capacity of the positive electrode material, and enhance the structural stability of the positive electrode material.
[0045] In some embodiments, the average particle size of the primary particles in the positive electrode material is 1 μm to 5 μm, specifically 1.0 μm, 1.2 μm, 1.4 μm, 1.5 μm, 1.8 μm, 2.0 μm, 2.4 μm, 2.8 μm, 3.0 μm, 3.5 μm, 3.8 μm, 4.0 μm, 4.2 μm, 4.5 μm, 4.8 μm or 5.0 μm, etc., and of course, it can also be other values within the above range, which is not limited here. In the present application, controlling the average particle size of the primary particles within the above range can reduce the impedance of the positive electrode material, improve the lithium ion transmission efficiency, and help improve the capacity of the positive electrode material.
[0046] In some embodiments, the positive electrode material is a single crystal material, and the positive electrode material includes single crystal particles, and the single crystal particles are particles with the same orientation. It should be specially noted that the "single crystal material" known to those skilled in the art is not a "single crystal" in the strict sense. In crystallography, an ideal single crystal refers to a crystal with completely the same arrangement and direction. However, due to impurities, strain and crystal defects, ideal single crystals are very rare and difficult to produce in reality. Therefore, the single crystal material known in the art is actually more of a "single crystal morphology" positive electrode material, which only shows a single crystal-like large particle size in size, which is different from the polycrystalline particles composed of many small particles.
[0047] The single crystal grain in the present application may be a single particle composed of one primary particle. The above-mentioned single crystal positive electrode material may also contain a small amount of "quasi-secondary particles" formed by the adhesion of several primary particles. "Primary particle" refers to the smallest particle unit identified when observing the positive electrode active material through a scanning electron microscope.
[0048] It should be noted that the difference between single crystal positive electrode materials and polycrystalline positive electrode materials (i.e., polycrystalline secondary particles) is that the smallest particle of polycrystalline secondary particles is a secondary particle formed by the agglomeration of nano-scale particles. For single crystal positive electrode materials, the smallest particle is usually a single particle of micrometer size. Generally speaking, in addition to the EBSD test method, it is also possible to determine whether the obtained positive electrode product is a single crystal material by characterization methods such as scanning electron microscopy (SEM). For example, for single crystal positive electrode materials, the morphology of single crystal particles can be characterized by SEM, and it can be seen that the shape of single crystal particles is generally regular or irregular spherical, and there is no significant particle agglomeration. The orientation of single crystal positive electrode materials can also be characterized by EBSD. Through EBSD, it can be observed that the color in at least one grain is the same, so as to judge that the orientation in at least one grain is the same, and the grains with the same orientation are single crystals. It should be specifically noted that the "single crystal positive electrode material" known to those skilled in the art is not a "single crystal" in the strict crystallographic sense. In crystallography, an ideal single crystal refers to a crystal with completely the same arrangement and direction. However, due to impurities, strains and crystal defects, ideal single crystals are very rare and difficult to produce in the laboratory. Therefore, the single crystal cathode materials known in the art are actually more "single crystal morphology" cathode materials, which only show the size of large single crystal particles and are different from polycrystalline particles composed of many small primary particles.
[0049] In some embodiments, during the first cycle of charge and discharge, the degree of structural recovery δ of the positive electrode material satisfies: 100.00% ≥ δ ≥ 99.70%; wherein δ = θ1 / θ2*100%, θ1 is the diffraction angle of the positive electrode material at the (003) crystal plane diffraction peak measured by X-ray diffraction at the beginning of the first cycle of charging, and θ2 is the diffraction angle of the positive electrode material at the (003) crystal plane diffraction peak measured by X-ray diffraction at the end of the first cycle of discharge. Specifically, δ can be 99.7%, 99.8%, 99.85%, 99.9%, 99.95% or 100.00%, etc., and of course, it can also be other values within the above range, which is not limited here. It can be understood that the degree of structural recovery of the positive electrode material is controlled within the above range. It can be seen that during the charge and discharge cycle, the crystal structure of the positive electrode material can remain stable, the irreversible phase change of the positive electrode material is reduced, and the lattice structure attenuation is greatly improved, which is conducive to maintaining the cyclic structural stability of the positive electrode material.
[0050] In some embodiments, the specific surface area of the positive electrode material is 0.5 m 2 / g~1.5m 2 / g; specifically, it can be 0.5m 2 / g, 0.6m 2 / g, 0.8m 2 / g, 1.0m 2 / g, 1.1m 2 / g, 1.2m 2 / g, 1.3m 2 / g, 1.4m 2 / g or 1.5m 2 / g, etc., and of course, it can also be other values within the above range, which is not limited here. By controlling the specific surface area of the positive electrode material within the above range, the positive electrode material can exhibit higher capacity, first coulombic efficiency, cycle stability and lower gas production.
[0051] In some embodiments, the tap density of the positive electrode material is 1.0 g / cm 3 ~3.0g / cm 3 , specifically 1.0 g / cm 3 , 1.2g / cm 3 , 1.3g / cm 3 , 1.4g / cm 3 , 1.5g / cm 3 , 1.6g / cm 3 , 1.7g / cm 3 , 1.8g / cm 3 , 1.9g / cm 3 , 2.0g / cm 3 , 2.1g / cm 3 , 2.2g / cm 3 , 2.4g / cm 3 , 2.5g / cm 3 , 2.8g / cm 3 or 3.0g / cm 3 Of course, it can be other values within the above range, which is not limited here. Controlling the tap density of the positive electrode material within the above range is conducive to improving the processing performance of the material and increasing the energy density of the battery.
[0052] In some embodiments, the compaction density of the positive electrode material is 2.5 g / cm 3 ~3.5g / cm 3 , specifically 2.5 g / cm 3 , 2.6g / cm 3 , 2.7g / cm 3 , 2.8g / cm 3 , 2.9g / cm 3 、3.0g / cm 3、3.1g / cm 3 、3.2g / cm 3 、3.4g / cm 3 or 3.5g / cm 3 Of course, it can be other values within the above range, which is not limited here. Controlling the compaction density of the positive electrode material within the above range is beneficial to improving the energy density of the battery.
[0053] In some embodiments, the bulk density of the positive electrode material is 0.5 g / cm 3 ~1.5g / cm 3 , specifically 0.5 g / cm 3 , 0.6g / cm 3 , 0.7g / cm 3 , 0.8g / cm 3 , 0.9g / cm 3 , 1.0g / cm 3 , 1.1g / cm 3 , 1.2g / cm 3 , 1.4g / cm 3 or 1.5g / cm 3 Of course, it can be other values within the above range, which is not limited here. Controlling the bulk density of the positive electrode material within the above range is beneficial to improving the energy density of the battery.
[0054] In a second aspect, the present application provides a method for preparing a positive electrode material, comprising the following steps:
[0055] S10, subjecting the hydroxide precursor of the positive electrode material to a nitration annealing treatment to obtain an oxide precursor containing nitrate ions;
[0056] S20, subjecting a mixture of an oxide precursor containing nitrate ions and a lithium source to a sintering treatment, and crushing the sintering product to obtain a positive electrode material, wherein the mass content of free nitrate in the positive electrode material is Qppm, 10≤Q≤100; the number of particles with a particle size less than 1μm in the positive electrode material accounts for R%, 8≤R≤16.
[0057] The preparation method of the positive electrode material provided in the present application is to subject the hydroxide precursor of the positive electrode material to nitration annealing treatment to obtain an oxide precursor containing nitrate ions; wherein, the nitration annealing treatment refers to annealing treatment after keeping warm in a nitric acid atmosphere for a certain period of time, so that the oxide precursor contains an appropriate amount of nitrate ions. A mixture containing an oxide precursor containing nitrate ions and a lithium source is subjected to a sintering treatment. The reaction activity of the oxide precursor during the sintering process is lower than that of the hydroxide precursor, which is conducive to the uniform growth of primary particles, the increase of the particle size of the primary particles, and the decrease in the number of particles with a particle size of less than 1 μm. The mass content of free nitrate ions in the positive electrode material prepared by the present application is between 10ppm and 100ppm, and the number of particles with a particle size of less than 1 μm in the positive electrode material is controlled to account for between 8% and 16%. An appropriate amount of small particles can improve the stacking tightness between the positive electrode material particles without causing too many side reactions, which can improve the transmission of lithium ions, reduce the internal resistance of the positive electrode material, reduce the lithium ion transmission barrier, and improve the lithium extraction efficiency of the positive electrode material. With the synergistic effect of an appropriate amount of free nitrate ions and particles with a particle size of less than 1 μm, the high voltage resistance and high capacity of the positive electrode material can be improved, while the lithium ion transmission efficiency of the positive electrode material can be enhanced and the cycle stability of the positive electrode material can be improved.
[0058] The preparation method of the present application is described in detail below with reference to the examples:
[0059] Before step S10, the method further includes:
[0060] S01, preparing a salt solution of nickel, manganese and N elements into a mixed solution according to a certain stoichiometric ratio, adjusting the pH value of the mixed solution, and obtaining a hydroxide precursor of the positive electrode material by a coprecipitation method. The N element may be Mn element and / or Al element.
[0061] In some embodiments, the stoichiometric ratio of nickel, cobalt, and N elements meets the following conditions: 0.5≤Ni<1, 0<Co≤0.2, 0<N≤0.4; the molar ratio of Ni:Co:N can be 0.60:0.10:0.30, 0.67:0.05:0.28, or 0.90:0.5:0.05, etc. The N element can be a Mn element and / or an Al element.
[0062] In some embodiments, the salt solution is sulfate. Compared with the conventional co-precipitation method, the present application adopts a sulfate system to prepare a hydroxide precursor.
[0063] In some embodiments, the pH value of the mixed solution is 7 to 14, specifically 7, 7.5, 8, 8.5, 9, 9.5, 10, 11, 12, 13 or 14, etc., and of course it can also be other values within the above range, which is not limited here.
[0064] In some embodiments, the regulator used in the co-precipitation method can be ammonia water, citric acid, ethylene glycol, etc., so as to help the hydroxide in the mixed solution to be precipitated and separated from the mixed solution.
[0065] In other embodiments, before step S10, a spray pyrolysis method may be used to react the salt in the mixed solution to form an oxide precursor.
[0066] In other embodiments, a hydroxide precursor purchased from the market may also be used.
[0067] S10, subjecting the hydroxide precursor of the positive electrode material to nitration annealing to obtain an oxide precursor containing nitrate ions.
[0068] In some embodiments, the nitration annealing treatment is performed by maintaining the temperature for a certain period of time in a mixed atmosphere containing nitric acid.
[0069] In some embodiments, the volume concentration of nitric acid in the mixed atmosphere is 1% to 3%; specifically, it can be 1%, 1.5%, 2%, 2.5%, 2.8 or 3.0%, etc., and of course, it can also be other values within the above range, which is not limited here.
[0070] In some embodiments, the mass content of oxygen in the mixed atmosphere is less than 1.0 ppm. Too much oxygen will cause the oxide precursor grains to grow too fast, which is not conducive to maintaining the uniformity of the precursor particles and leads to a decrease in the reactivity of the oxide precursor.
[0071] In some embodiments, the mixed atmosphere includes nitric acid vapor and water vapor.
[0072] In some embodiments, the temperature of the nitration annealing treatment is 200°C to 800°C, specifically 200°C, 250°C, 300°C, 350°C, 480°C, 550°C, 600°C, 630°C, 650°C, 680°C, 700°C, 750°C, 780°C or 800°C, etc., and of course it can also be other values within the above range, which is not limited here.
[0073] In some embodiments, the heating rate of the nitration annealing treatment is 0.5°C / min to 3°C / min, specifically 0.5°C / min, 0.8°C / min, 1.0°C / min, 1.5°C / min, 1.8°C / min, 2.0°C / min, 2.5°C / min or 3.0°C / min, etc., and of course it can also be other values within the above range, which is not limited here.
[0074] In some embodiments, the holding time of the nitration annealing treatment is 3 h to 10 h, specifically 3 h, 4 h, 5 h, 6 h, 7 h, 8 h, 9 h or 10 h, etc., and of course, it can also be other values within the above range, which is not limited here.
[0075] In some embodiments, the ambient pressure during the nitration annealing treatment is lower than the pressure of the mixed atmosphere.
[0076] In some embodiments, the ambient pressure during the nitration annealing treatment is 2.0 kPa to 4.0 kPa, specifically 2.0 kPa, 2.2 kPa, 2.5 kPa, 2.8 kPa, 3.0 kPa, 3.2 kPa, 3.5 kPa or 4.0 kPa, etc., and may be other values within the above range, which is not limited here.
[0077] In the present application, by controlling the process parameters such as the ambient pressure, holding time, and annealing temperature during the nitration annealing treatment, it is beneficial to form an appropriate amount of nitrate ions on the surface of the oxide precursor.
[0078] In some embodiments, the chemical formula of the oxide precursor of the positive electrode material is Ni a Co b N c M e O, wherein 0<a<1, 0<b<1, 0<c<1, 0≤e<1, and a+b+c+e=1, N includes at least one of Mn and Al, and M includes at least one of Zr, Mg, W, Mo, Ti, Ba, Sr, Cr, Zn, Y, V, Cu, B, and Nb.
[0079] The oxide precursor containing nitrate ions has lower reactivity than the hydroxide precursor. During the sintering process of the oxide precursor and the lithium salt, the diffusion resistance of the lithium salt is slightly larger, which is conducive to the generation of an appropriate amount of primary particles with smaller particle size, thereby improving the compaction density of the positive electrode material.
[0080] S20, performing a primary sintering treatment on the mixture including the oxide precursor containing nitrate ions and the lithium source, and crushing the primary sintering product to obtain a positive electrode material.
[0081] In some embodiments, the lithium source includes at least one of lithium hydroxide, lithium carbonate, lithium nitrate, lithium acetate, lithium sulfate and lithium oxalate. Preferably, the lithium salt is lithium carbonate.
[0082] In some embodiments, the added amounts of the lithium source and the oxide precursor satisfy: the ratio of the molar amount of Li to the total molar amount of all metals in the oxide precursor is (0.87-1.25):1, specifically 0.87:1, 0.89:1, 0.92:1, 0.95:1, 0.98:1, 1.02:1, 1.05:1, 1.1:1, 1.17:1 or 1.25:1, etc., and of course it can also be other values within the above range, which is not limited here.
[0083] In some embodiments, the mixture further includes a dopant containing metal M, and the metal M includes at least one of Zr, Mg, Ti, Ba, Sr, Cr, Zn, V, Cu, Nb, Mo, Y and W. Specifically, the dopant may contain a salt or oxide of the metal M.
[0084] In some embodiments, the dopant includes at least one of Nb2O5, Nb2O3, MoO3, WO2, WO3, V2O5, V2O3, Sr(OH)2, SrO, SrCO3, TiO2, ZrO2, Zr(OH)4, Y2O3, BaO, Cr2O3, ZnO, CuO, Ta2O5, CaO, Sb2O3, Sb2O5, H3BO3, MgO and Mg(OH)2. Preferably, the dopant containing metal M is a compound of Zr or Ti.
[0085] In some embodiments, the mixing conditions for obtaining the mixture are: solid phase mixing at 10° C. to 50° C. for 0.3 h to 3 h.
[0086] In some embodiments, the temperature of solid phase mixing can be 10°C, 15°C, 20°C, 25°C, 30°C, 35°C, 40°C, 45°C or 50°C, and the time of solid phase mixing can be 0.3h, 0.4h, 0.5h, 0.6h, 0.8h, 1h, 1.5h, 1.8h, 2.5h or 3h, etc., and of course, it can also be other values within the above range, which are not limited here. Preferably, the temperature of solid phase mixing is 10°C to 35°C.
[0087] In some embodiments, the mixing device may be at least one of a ball mill, a three-dimensional mixer, a high-speed mixer, and a VC mixer.
[0088] In some embodiments, the primary sintering process includes sequentially performing a first heating stage, a second heating stage, a first cooling stage and a third constant temperature stage, the temperature of the first heating stage is 300°C to 600°C, the temperature of the second heating stage is 720°C to 1000°C, the temperature of the first cooling stage is 500°C to 700°C, and the temperature of the third constant temperature stage is 720°C to 1000°C.
[0089] In some embodiments, the temperature of the first heating stage can be 300°C, 350°C, 380°C, 400°C, 430°C, 450°C, 500°C, 550°C, 580°C or 600°C, etc. The time of the first heating stage is 3h to 5h, and can be 3h, 3.5h, 4h, 4.5h or 5h, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable. The temperature of the first heating stage is relatively low, and the lithium source can be fully melted and react with the oxide precursor.
[0090] In some embodiments, the heating rate in the first heating stage is 15°C / min to 20°C / min, specifically 15°C / min, 16°C / min, 17°C / min, 18°C / min, 19°C / min or 20°C / min, etc. Of course, it can also be other values within the above range, which is not limited here.
[0091] In some embodiments, the temperature of the second heating stage can be 720°C, 770°C, 800°C, 880°C, 900°C or 1000°C, etc., but is not limited to the listed values, and other values not listed in the numerical range are also applicable. The time of the second heating stage is 4h to 12h, and can be 4h, 5h, 6h, 8h, 9h, 10h, 11h or 12h, etc., but is not limited to the listed values, and other values not listed in the numerical range are also applicable. The crystals of the positive electrode material are initially grown in the second heating stage, while reducing excessive growth of particles.
[0092] In some embodiments, the heating rate in the second heating stage is 0.5℃ / min to 3℃ / min, specifically 0.5℃ / min, 0.6℃ / min, 0.7℃ / min, 1.0℃ / min, 1.2℃ / min, 1.5℃ / min, 2.0℃ / min, 2.2℃ / min, 2.5℃ / min, 2.8℃ / min or 3℃ / min, etc. Of course, it can also be other values within the above range, which is not limited here.
[0093] In some embodiments, the temperature of the first cooling stage can be 500°C, 550°C, 580°C, 600°C, 620°C, 650°C, 680°C, 690°C or 700°C, etc., but is not limited to the listed values, and other values not listed in the numerical range are also applicable. The time of the first cooling stage is 2h to 6h, and can be 2h, 3h, 4h, 5h, 5.5h or 6h, etc., but is not limited to the listed values, and other values not listed in the numerical range are also applicable. The cooling process can rearrange the atoms on the surface of the grown primary particles to form a surface structure with lower free energy and higher chemical stability.
[0094] In some embodiments, the cooling rate in the first cooling stage is 0.5℃ / min to 3℃ / min, specifically 0.5℃ / min, 0.6℃ / min, 0.7℃ / min, 1.0℃ / min, 1.2℃ / min, 1.5℃ / min, 2.0℃ / min, 2.2℃ / min, 2.5℃ / min, 2.8℃ / min or 3℃ / min, etc., and of course it can also be other values within the above range, which is not limited here.
[0095] In some embodiments, the temperature of the third constant temperature stage can be 720°C, 770°C, 800°C, 880°C, 900°C or 1000°C, etc., but is not limited to the listed values, and other values not listed in the numerical range are also applicable. The time of the third constant temperature stage is 1h to 3h, and can be 1h, 1.5h, 2h, 2.5h or 3h, etc., but is not limited to the listed values, and other values not listed in the numerical range are also applicable. In this constant temperature stage, the crystal structure of the primary particles of the positive electrode material is fully grown to ensure the structural stability of the primary particles.
[0096] In some embodiments, the heating rate of the third constant temperature stage is 0.5℃ / min to 3℃ / min, specifically 0.5℃ / min, 0.6℃ / min, 0.7℃ / min, 1.0℃ / min, 1.2℃ / min, 1.5℃ / min, 2.0℃ / min, 2.2℃ / min, 2.5℃ / min, 2.8℃ / min or 3℃ / min, etc., and of course it can also be other values within the above range, which is not limited here.
[0097] In some embodiments, the sintered product is cooled to room temperature after the third constant temperature stage.
[0098] In some embodiments, the primary sintering process is performed in an oxygen-containing atmosphere, and the oxygen content in the oxygen-containing atmosphere is ≥ 95%.
[0099] In some embodiments, when the dopant containing metal M is a compound of Zr or Ti, the temperature of the primary sintering treatment is 800° C. to 900° C., and the holding time is 8 h to 10 h.
[0100] In some embodiments, the method further comprises: mixing the crushed base material with a coating agent containing metal M, and then performing a secondary sintering process to obtain a positive electrode material.
[0101] In some embodiments, the crushing method includes at least one of a double roller, a plowshare mixer / crusher, and a jet mill.
[0102] In some embodiments, the coating agent containing metal M, M is selected from at least one of Zr, Mg, Ti, Ba, Sr, Cr, Zn, V, Cu, Nb, Mo, Y and W. The coating agent containing metal M may be a salt or oxide of metal M. Preferably, the coating agent containing metal M includes a Nb compound and / or a W compound.
[0103] In some embodiments, the secondary sintering process is performed in an oxygen-containing atmosphere, and the oxygen content in the oxygen-containing atmosphere is ≥ 95%.
[0104] In some embodiments, the temperature of the secondary sintering treatment is 300°C to 800°C, specifically 300°C, 320°C, 330°C, 350°C, 380°C, 400°C, 450°C, 500°C, 550°C, 650°C, 700°C or 800°C, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0105] In some embodiments, the holding time of the secondary sintering treatment is 6h to 24h, specifically 6h, 8h, 10h, 12h, 15h, 18h or 24h, etc., but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0106] In some embodiments, when the coating agent containing metal M includes a Nb compound and / or a W compound, the temperature of the secondary sintering treatment is 500° C. to 600° C., and the holding time of the secondary sintering treatment is 6 h to 8 h.
[0107] In some embodiments, the preparation method further comprises cooling, shaping and screening the product after secondary sintering. The shaping comprises at least one of crushing, grinding, ball milling or gas crushing.
[0108] In some embodiments, the sieving uses a screen with a mesh size of 300 to 400 mesh.
[0109] In a third aspect, the present application provides a battery, the battery comprising the positive electrode material of the first aspect or the positive electrode material prepared according to the preparation method of the positive electrode material.
[0110] The battery provided in the present application may be a secondary battery (such as a lithium-ion battery, a sodium-ion battery, etc.), including a housing, an electrode assembly, and an electrolyte. The electrode assembly and the electrolyte are both located in the housing. The housing may be a packaging bag encapsulated by an encapsulation film (such as an aluminum-plastic film), such as a soft-pack battery.
[0111] In other embodiments, the secondary battery may also be a steel shell battery, an aluminum shell battery, etc.
[0112] Figure 1A schematic diagram of the discharge state of a battery provided in an embodiment of the present application, such as Figure 1 As shown, the battery includes a shell and an electrode assembly, the electrode assembly includes a positive electrode sheet 1, a negative electrode sheet 2 and a separator 3, and the separator 3 is arranged between the positive electrode sheet 1 and the negative electrode sheet 2. The electrode assembly can be a laminated structure, which is formed by alternately stacking the positive electrode sheet 1, the separator 3 and the negative electrode sheet 2 in sequence.
[0113] In other embodiments, the electrode assembly may also be a winding structure, which is formed by stacking a positive electrode sheet, a separator, and a negative electrode sheet in sequence and then winding them.
[0114] In some embodiments, the positive electrode sheet 1 includes a positive electrode current collector 11 and a positive electrode active material layer 12 disposed on at least one surface of the positive electrode current collector 11 .
[0115] In some embodiments, the positive electrode current collector 11 may be aluminum foil or nickel foil, or any composite current collector disclosed in the prior art, such as but not limited to the current collector formed by combining the aforementioned conductive foil (aluminum foil or nickel foil, etc.) and a polymer substrate. The positive electrode active material layer 12 comprises a positive electrode active material, a conductive agent, and a binder, wherein the positive electrode active material is the positive electrode material of the first aspect described above or a positive electrode material prepared according to the preparation method of the positive electrode material described above.
[0116] In some embodiments, the negative electrode sheet 2 includes a negative electrode current collector 21 and a negative electrode active material layer 22 disposed on at least one surface of the negative electrode current collector.
[0117] In some embodiments, the negative electrode current collector 21 can be made of at least one of copper foil, nickel foil, stainless steel foil, titanium foil or a carbon-based current collector, or can be any composite current collector disclosed in the prior art, such as but not limited to a current collector formed by combining the aforementioned conductive foil and a polymer substrate.
[0118] In some embodiments, the negative electrode active material layer 22 includes a negative electrode material, and the negative electrode material includes but is not limited to artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material can be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material can be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries can also be used. These negative electrode active materials can be used alone or in combination of two or more.
[0119] The battery provided in the embodiment of the present application has the advantages of high capacity, high initial efficiency, long cycle life, excellent rate performance and low expansion. The battery can be a lithium ion battery, a sodium ion battery, a solid electrolyte battery, etc., which is not limited here.
[0120] The following is a further description of the embodiments of the present invention in multiple embodiments. The embodiments of the present invention are not limited to the following specific embodiments. The embodiments can be appropriately modified within the scope of the unchanged main rights.
[0121] Test method:
[0122] (1) Test of free nitrate content in positive electrode materials
[0123] 1. Weigh about 0.7g of sample into a 70mL beaker, accurate to 0.0001g;
[0124] 2. Accurately measure 50mL of ultrapure water in a 50mL volumetric flask, first add a small amount of ultrapure water (about 7mL) to the sample, stir evenly with a glass rod, then add the remaining ultrapure water, stir evenly, ultrasonicate for 3 minutes, and let stand for about 17 minutes to allow the sample to precipitate;
[0125] 3. Use a 1mL sterile syringe to draw the sample supernatant, inject it into the ion chromatograph through a disposable filter head for testing; ion chromatograph model: Thermo Scientific Dionex ICS-6000; chromatographic setting conditions: eluent concentration: 25mmol / L; eluent flow rate: 0.3mL / min; column temperature: 30±1℃; detection cell temperature: 35±1℃; suppressor current: 26mA; chromatographic column: anion exchange column (4*250mm, AS11-HC); data acquisition: after the baseline is stable (the signal value change is less than 0.1μS / 20min), click data acquisition and the analysis will begin.
[0126] 4. Result calculation: The calculation formula is Q = Ci*V / M, where Q is the content of element i in the sample, mg / kg; Ci is the concentration of element i in the sample solution, mg / L; V is the volume of the sample solution, ml; M is the mass of the sample, g. In the anion test, by measuring the content of N element, it can be converted into nitrate NO3 by the ion molecular weight. - The content of the substance is automatically converted by the test software provided with the instrument.
[0127] (2) The proportion of particles with a particle size less than 1 μm in the positive electrode material
[0128] 1) Use a cotton swab to pick up a small amount of powder sample and apply it evenly and densely on the conductive glue; use a hair dryer to slowly blow in the direction where there are no other samples, and when it is confirmed to be evenly applied on the surface, blow strongly for more than 10 times until there is no residual powder;
[0129] 2) Set the basic conditions of SEM: voltage 5 kV, current 12 mA, magnification 2k, contrast and brightness are adjusted using the auto key, and the measurement position is set to the part with 400 to 1200 particles (center value 800 particles);
[0130] 3) Save the SEM image. Each sample is measured under this condition for 10 photos. All the pictures are imported into MetisVision software and manually identified. The bottom edge size and boundary size are adjusted according to the specific SEM image. The particles with a size range of dmin-dmax, an aspect ratio of 0-9.0, and an area ratio of 0-1.00 are identified, and the number of particles smaller than 1 μm, the particle size, and other information are counted.
[0131] 4) It is statistically determined that the number of particles with a particle size less than 1 μm in the positive electrode material accounts for R%.
[0132] (3) IPC test method for positive electrode materials:
[0133] Equipment: Agilent 5110ICP-OES plasma inductively coupled electrochemical analyzer.
[0134] Method: Take 0.3g sample and add aqua regia for digestion. After cooling and constant volume, take 1mL and dilute 100 times to test the main elements Li / Ni / Co / Mn, and the mother liquor is used to test the impurity elements.
[0135] (4) XRD test method of positive electrode materials:
[0136] Equipment: XPert Powder (PANalytical) or Bruker's X-ray diffraction tester products.
[0137] Method: Fill the powder sample into the sample slot, flatten the upper surface with a glass sheet, and ensure that the upper surface of the sample is parallel to the slot edge. The scanning range is 2θ = 10-90 ° C, and the total scanning time is not less than 5 minutes. After the scan is completed, open it with jade software and automatically search for peaks through Analysis → Find Peaks to identify the position and height of the diffraction peak.
[0138] (5) Testing method for particle size of positive electrode materials:
[0139] The particle size distribution range of the positive electrode material was tested by Malvern laser particle size analyzer to obtain D 90 , D 50 and D 10 Hitachi S4800 scanning electron microscope was used to take 5 views of samples at different positions at 3000 times magnification, and NanoMeasure software was used to measure the primary particle size of the positive electrode material in each view. The average value of the 5 primary particle sizes was taken as the average particle size of the primary particles.
[0140] (6) Testing method for specific surface area of positive electrode material:
[0141] Equipment: Micromeritics Tristar 3020 surface area and pore size analyzer was used to test the surface area of the positive electrode material.
[0142] Method: Weigh the mass of the empty sample tube m1; take 3g of sample and add it to the sample tube through a long-necked funnel; vacuum degas at 300℃ for 1h, and weigh the mass of the sample tube m2 after cooling; the mass of the sample is m=m2-m1. The sample tube is placed in liquid nitrogen, and the nitrogen adsorption amount V of the sample is measured at a series of relative pressures P / P0 to obtain the adsorption isotherm. Among them, P / P0 is set to 0.05 / 0.1 / 0.15 / 0.20 / 0.25 / 0.30. Fit the isothermal adsorption curve, calculate the monolayer saturated adsorption amount Vm according to the slope and intercept, and then calculate the specific surface area according to Vm.
[0143] (7) Kanta tap density test of positive electrode material:
[0144] Equipment: American Quantacon tap density tester (model: DAT-4-220)
[0145] Method: Clean the measuring cylinder and weigh the mass of the measuring cylinder as m1; add about 50g of sample into the measuring cylinder, try to make the sample surface level, and wipe the surrounding area with a paper towel; weigh the total mass of the sample and the measuring cylinder as m2; place the measuring cylinder on the vibration table and fix it with three symmetrical fixed feet; turn on the instrument and set the vibration number to 5000 times; turn on the vibration switch, and the instrument will automatically stop after vibrating the specified number of times; take out the measuring cylinder and read the volume of the sample. If the sample surface is horizontal after vibration, read the volume directly; if it is in a diagonal state, take the average value V of the readings at the highest and lowest points; tap density = (m2-m1) / V.
[0146] (8) Compacted density test of positive electrode materials:
[0147] The compaction density of the positive electrode material is tested using the American carver 4350, and the steps are as follows: weigh 1g of sample and put it into a mold and press it with a pressure of 3T for 30s. After pressing, the height is tested to calculate the compaction.
[0148] (9) Bulk density test of positive electrode materials:
[0149] Equipment: Beijing Zheyuan Bulk Density Tester BT101
[0150] Method: Take an appropriate amount of sample and allow it to flow naturally into the distribution box, alternately pass through four glass plates with an inclined angle of 25° and a square funnel in the distribution box, and flow into a cylindrical cup of known volume (25 ml). Finally, weigh the mass of the powder in the cylindrical cup.
[0151] (10) Particle size test of positive electrode materials:
[0152] Equipment: Mastersizers 3000.
[0153] Method: Before testing, the laser intensity should be observed. If it is lower than 70%, the testing department should be notified to clean the lens and water inlet and outlet hoses; after starting to measure the background, perform external ultrasound to dissolve the sample (using the instrument to automatically align the light and measure the background to perform external ultrasound to dissolve the sample can reduce the probability of the sample being contaminated by long-term storage); perform external ultrasound for 30 seconds while stirring back and forth; before adding the sample, add 3 drops of sodium hexametaphosphate to the sample pool, stir, and pour all into the sample pool at once; when all the sample is poured in, wait for 10 seconds and click to start the sample test; the laser shading degree should be maintained between 7-12%.
[0154] (11) SEM test of positive electrode materials:
[0155] Equipment: Hitachi S4800 scanning electron microscope, OXFORD Instrument's energy dispersive spectrometer.
[0156] SEM method: When testing powder samples, use tweezers or other tools to pick up the powder sample, spread it flat on the conductive glue and flatten it, and test it under 5kV / 10mA electron beam conditions.
[0157] (12) Electrochemical performance test:
[0158] The positive electrode materials obtained in the examples and comparative examples were assembled into button cells: the positive electrode material, conductive carbon and polyvinylidene fluoride (PVDF) were added into N-methyl-2-pyrrolidone (NMP) at a mass ratio of 96:2:2, and the positive electrode slurry was uniformly mixed and coated on the positive electrode current collector and vacuum dried to form a positive electrode sheet (the compacted density of the sheet was 2.8 g / cm 3 ), with lithium sheet as negative electrode, assembled into 2016 button cells in a glove box.
[0159] In the discharge range of 3.0V-4.3V and the condition of 1C theoretical capacity of 250mAh / g, the battery was tested using the CT2001A battery testing system of Wuhan Blue Electric Electronics Co., Ltd. The test results are shown in Table 1.
[0160] (13) Structural recovery test:
[0161] Electrochemical in situ XRD was used with Bruker D8 Advance (Cu target) and BlueDian (5mA, 5V) equipment to test the structural changes during the charge and discharge process. The charge and discharge voltage range was 2.8V-4.35V. The XRD spectrum was then fitted with Jade software to obtain the diffraction angles corresponding to the (003) peaks at the beginning and end of charge and discharge.
[0162] Example 1
[0163] (1) Dissolve metal nickel, metal manganese and metal cobalt in sulfuric acid to form a sulfate solution; prepare the three solutions according to the stoichiometric ratio of Ni:Co:Mn=6:1:3 to form a mixed solution with a total concentration of Ni, Co and Mn of 2 mol / L. Continuously introduce 1 mol / L NaOH solution and 0.5 mol / L ammonia water into the mixed solution to control the pH value within the range of 11±0.2. 50 When the particle size reaches 8 μm, the reaction is stopped, and the precipitate is centrifuged, washed, and dried to obtain a hydroxide precursor of the positive electrode material.
[0164] (2) The positive electrode material hydroxide precursor is placed in an atmosphere with a nitric acid concentration of 2% for nitration annealing; the atmosphere contains only HNO3 and H2O, and the O2 content is less than 1.0 ppm; the temperature is heated to 600°C at a heating rate of 2°C / min and kept at this temperature for 6 hours for annealing; during the annealing process, the pressure of the reaction environment is controlled at 3.0 kPa to obtain an oxide precursor, whose general chemical formula is Ni 0.6 Co 0.1 Mn 0.3 O x (The content deviation of each element is within ±1%).
[0165] (3) The oxide precursor is mixed with Li2CO3 at a Li / Me (Me is the sum of Ni, Co, and Mn) molar ratio of 1.02:1, and ZrO2 with a mass content of 2000 ppm relative to the oxide precursor is added, and placed in an atmosphere electric heating furnace or a Joule heat reactor, using an oxygen atmosphere, and the reaction gas pressure is controlled at 10 Pa; the temperature is increased from room temperature to 500°C in the first heating stage at a heating rate of 20°C / min, and kept at this temperature for 4 hours; the temperature is increased to 700°C in the second heating stage at a heating rate of 2°C / min, and kept at this temperature for 6 hours; the temperature is decreased to 500°C in the first cooling stage at a cooling rate of 1°C / min, and kept at this temperature for 4 hours; the temperature is increased to 900°C in the third constant temperature stage at a heating rate of 1°C / min, and kept at this temperature for 2 hours; the temperature is decreased from the fourth platform temperature to room temperature at a cooling rate of 2°C / min to obtain a matrix material.
[0166] (4) The base material was crushed and mixed with 1000 ppm of Nb2O5, and then secondary sintered at 500°C for 6 h in an oxygen atmosphere to obtain a positive electrode material.
[0167] The general chemical formula of the positive electrode material is Li 1.02 Ni 0.6 Co 0.1 Mn 0.297 Zr 0.002 Nb 0.001O2.
[0168] Example 2
[0169] The difference from Example 1 is:
[0170] (1) Dissolve metal nickel, metal manganese and metal cobalt in sulfuric acid to form a sulfate solution; prepare the three solutions according to the stoichiometric ratio of Ni:Co:Mn=67:5:28 to form a mixed solution with a total concentration of Ni, Co and Mn of 2 mol / L. Add appropriate amounts of citric acid and ethylene glycol to the mixed solution, control the pH value within the range of 8±0.2, and then place it in a reactor and keep it at 180°C for 24 hours to obtain a gel precipitate, centrifuge the gel precipitate, wash and dry it, and obtain a gel precursor.
[0171] (2) placing the gel precursor in an atmosphere with a nitric acid concentration of 2% for nitration annealing; the atmosphere contains only HNO3 and H2O, and the O2 content is less than 1.0 ppm; heating to a temperature of 600°C at a heating rate of 2°C / min, and annealing is performed for 6 hours; during the annealing process, the pressure of the reaction environment is controlled at 3.0 kPa to obtain an oxide precursor with a general chemical formula of Ni 0.67 Co 0.05 Mn 0.28 O x (The content deviation of each element is within ±1%).
[0172] (3) The oxide precursor is mixed with Li2CO3 at a Li / Me (Me is the sum of Ni, Co, and Mn) molar ratio of 1.01:1, and TiO2 is added with a mass content of 1000 ppm relative to the oxide precursor. The subsequent sintering process is the same as step (3) of Example 1.
[0173] (4) The base material was crushed and mixed with 1500 ppm of Al2O3, and then secondary sintered at 500°C for 6 h in an oxygen atmosphere to obtain a positive electrode material.
[0174] The general chemical formula of the positive electrode material is Li 1.01 Ni 0.67 Co 0.05 Mn 0.274 Ti 0.002 Al 0.004 O2.
[0175] Example 3
[0176] The difference from Example 1 is:
[0177] (1) Dissolve metal nickel, metal manganese, and metal cobalt in sulfuric acid to form a sulfate solution; prepare the three solutions according to the stoichiometric ratio of Ni:Co:Mn=6:1:3 to form a mixed solution with a total concentration of Ni, Co, and Mn of 2 mol / L. Continue to add an appropriate amount of ammonia water to the mixed solution to control the pH value within the range of 7±0.2. 50 When the particle size reaches 8 μm, the reaction is stopped, and the obtained mixed solution is subjected to a spray pyrolysis process to obtain a hydroxide precursor of the positive electrode material.
[0178] (2) placing the positive electrode material hydroxide precursor in an atmosphere with a nitric acid concentration of 3% for nitration annealing; the atmosphere contains only HNO3 and H2O, and the O2 content is less than 1.0 ppm; heating to a temperature of 200°C at a heating rate of 3°C / min, and annealing is performed for 3 hours; during the annealing process, the pressure of the reaction environment is controlled at 2.0 kPa to obtain an oxide precursor, whose general chemical formula is Ni 0.6 Co 0.1 Mn 0.3 O x (The content deviation of each element is within ±1%).
[0179] The general chemical formula of the positive electrode material is Li 1.02 Ni 0.6 Co 0.1 Mn 0.297 Zr 0.002 Nb 0.001 O2.
[0180] Example 4
[0181] The difference from Example 1 is:
[0182] (3) The oxide precursor is mixed with Li2CO3 at a Li / Me (Me is the sum of Ni, Co, and Mn) molar ratio of 1.02:1, and ZrO2 with a mass content of 2000 ppm relative to the oxide precursor is added, and placed in an atmosphere electric heating furnace or a Joule heat reactor, using an oxygen atmosphere, and the reaction gas pressure is controlled at 10 Pa; the temperature is increased from room temperature to 300°C in the first heating stage at a heating rate of 20°C / min, and kept at this temperature for 5 hours; the temperature is increased to 900°C in the second heating stage at a heating rate of 2°C / min, and kept at this temperature for 4 hours; the temperature is decreased to 600°C in the first cooling stage at a cooling rate of 1°C / min, and kept at this temperature for 6 hours; the temperature is increased to 700°C in the third constant temperature stage at a heating rate of 0.5°C / min, and kept at this temperature for 6 hours; the temperature is decreased from the fourth platform temperature to room temperature at a cooling rate of 1°C / min to obtain a matrix material.
[0183] The general chemical formula of the positive electrode material is Li 1.02 Ni 0.6 Co 0.1 Mn0.297 Zr 0.002 Nb 0.001 O2.
[0184] Example 5
[0185] The difference from Example 4 is that:
[0186] (1) Dissolve metal nickel, metal manganese and metal cobalt in sulfuric acid to form a sulfate solution; prepare the three solutions according to the stoichiometric ratio of Ni:Co:Mn=90:5:5 to form a mixed solution with a total concentration of Ni, Co and Mn of 2 mol / L. Add appropriate amounts of citric acid and ethylene glycol to the mixed solution, control the pH value within the range of 7-9, and then place it in a reactor and keep it at 180°C for 24 hours to obtain a precipitate, which is centrifuged, washed and dried to obtain a positive electrode material hydroxide precursor.
[0187] (2) The positive electrode material hydroxide precursor is placed in an atmosphere with a nitric acid concentration of 1% for nitration annealing; the atmosphere contains only HNO3 and H2O, and the O2 content is <1.0ppm; the temperature is heated to 800°C at a heating rate of 0.5°C / min and kept at this temperature for 10 hours for annealing; during the annealing process, the pressure of the reaction environment is controlled at 2.0kPa to obtain an oxide precursor, whose general chemical formula is Ni 0.6 Co 0.1 Mn 0.3 O x (The content deviation of each element is within ±1%).
[0188] The general chemical formula of the positive electrode material is Li 1.02 Ni 0.9 Co 0.05 Mn 0.046 Zr 0.002 Nb 0.002 O2.
[0189] Example 6
[0190] The difference from Example 4 is that:
[0191] (3) The oxide precursor is mixed with Li2CO3 at a Li / Me (Me is the sum of Ni, Co, and Mn) molar ratio of 0.99:1.
[0192] The general chemical formula of the positive electrode material is Li 0.99 Ni 0.6 Co 0.1 Mn 0.297 Zr 0.002 Nb 0.001 O2.
[0193] Example 7
[0194] The difference from Example 4 is that:
[0195] (1) Dissolving metallic nickel, metallic manganese, and metallic cobalt in sulfuric acid respectively to form a sulfate solution; and configuring the three solutions into a mixed solution having a total concentration of Ni, Co, and Mn of 2 mol / L according to a stoichiometric ratio of Ni:Co:Mn=83:11:06.
[0196] Example 8
[0197] The difference from Example 4 is that:
[0198] (1) Dissolving metallic nickel, metallic manganese, and metallic cobalt in sulfuric acid respectively to form a sulfate solution; and configuring the three solutions into a mixed solution having a total concentration of Ni, Co, and Mn of 2 mol / L according to a stoichiometric ratio of Ni:Co:Mn=75:15:10.
[0199] Example 9
[0200] The difference from Example 2 is that:
[0201] (2) The positive electrode material hydroxide precursor is placed in an atmosphere with a nitric acid concentration of 2% for nitration annealing; the atmosphere contains only HNO3 and H2O, and the O2 content is less than 1.0 ppm; the temperature is heated to 600°C at a heating rate of 2°C / min and kept at this temperature for 8 hours for annealing; during the annealing process, the pressure of the reaction environment is controlled at 4.0 kPa to obtain an oxide precursor with a general chemical formula of Ni 0.67 Co 0.05 Mn 0.28 O x (The content deviation of each element is within ±1%).
[0202] Example 10
[0203] The difference from Example 1 is:
[0204] (3) The oxide precursor is mixed with Li2CO3 at a Li / Me (Me is the sum of Ni, Co, and Mn) molar ratio of 1.02:1, and ZrO2 with a mass content of 2000 ppm relative to the oxide precursor is added, and placed in an atmosphere electric heating furnace or a Joule heat reactor, using an oxygen atmosphere, and the reaction gas pressure is controlled at 10Pa; the temperature is increased from room temperature to 600°C in the first heating stage at a heating rate of 20°C / min, and kept at this temperature for 5 hours; the temperature is increased to 1000°C in the second heating stage at a heating rate of 2°C / min, and kept at this temperature for 3 hours; the temperature is decreased to 550°C in the first cooling stage at a cooling rate of 1°C / min, and kept at this temperature for 4 hours; the temperature is increased to 850°C in the third constant temperature stage at a heating rate of 1°C / min, and kept at this temperature for 3 hours; the temperature is decreased from the fourth platform temperature to room temperature at a cooling rate of 2°C / min to obtain a matrix material.
[0205] Embodiment 11
[0206] The difference from Example 1 is:
[0207] (1) Dissolve metal nickel, metal manganese and metal cobalt in nitric acid to form a nitrate solution; prepare the three solutions according to the stoichiometric ratio of Ni:Co:Mn=6:1:3 to form a mixed solution with a total concentration of Ni, Co and Mn of 2 mol / L. Continuously introduce a 1 mol / L NaOH solution and a 0.5 mol / L ammonia solution into the mixed solution to control the pH value within the range of 11±0.2. 50 When the particle size reaches 8 μm, the reaction is stopped, and the precipitate is centrifuged, washed, and dried to obtain a hydroxide precursor of the positive electrode material.
[0208] Example 12
[0209] The difference from Example 1 is:
[0210] (3) Mix the oxide precursor and Li2CO3 at a Li / Me (Me is the sum of Ni, Co, and Mn) molar ratio of 1.02:1, place in an atmosphere electric heating furnace or a Joule heat reactor, use an oxygen atmosphere, and control the reaction gas pressure at 10Pa; increase the temperature from room temperature to 500°C in the first heating stage at a heating rate of 20°C / min, and keep it warm for 4 hours; increase the temperature to 700°C in the second heating stage at a heating rate of 2°C / min, and keep it warm for 6 hours; decrease the temperature to 500°C in the first cooling stage at a cooling rate of 1°C / min, and keep it warm for 4 hours; increase the temperature to 900°C at the fourth platform at a heating rate of 1°C / min, and keep it warm for 2 hours; decrease the temperature from the third constant temperature stage to room temperature at a cooling rate of 2°C / min to obtain a matrix material.
[0211] (4) The base material was crushed and then secondary sintered at 500°C for 6 h in an oxygen atmosphere to obtain the positive electrode material.
[0212] The general chemical formula of the positive electrode material is Li 1.02 Ni 0.6 Co 0.1 Mn 0.3 O2.
[0213] Embodiment 13
[0214] The difference from Example 1 is:
[0215] (1) Dissolve metal nickel, metal aluminum, and metal cobalt in sulfuric acid to form a sulfate solution; prepare the three solutions according to the stoichiometric ratio of Ni:Co:Al=80:15:5 to form a mixed solution with a total concentration of Ni, Co, and Al of 2 mol / L. Add appropriate amounts of citric acid and ethylene glycol to the mixed solution, control the pH value within the range of 8±0.2, and then place it in a reactor and keep it at 180°C for 24 hours to obtain a gel precipitate, centrifuge the gel precipitate, wash and dry it, and obtain a gel precursor.
[0216] The general chemical formula of the positive electrode material is Li 1.02 Ni 0.8 Co 0.15 Al 0.046 Zr 0.002 Nb 0.002 O2.
[0217] Comparative Example 1
[0218] The difference from Example 1 is:
[0219] (2) The positive electrode material hydroxide precursor Ni 0.6 Co 0.1 Mn 0.3 (OH) x The temperature was heated to 200°C at a heating rate of 3°C / min and annealed for 3 h to obtain an oxide precursor with the general chemical formula of Ni 0.6 Co 0.1 Mn 0.3 O x (The content deviation of each element is within ±1%).
[0220] Comparative Example 2
[0221] The difference from Example 5 is:
[0222] (2) The positive electrode material hydroxide precursor is heated to 800°C at a heating rate of 0.5°C / min and kept at this temperature for 10 hours for annealing; during the annealing process, the pressure of the reaction environment is controlled at 2.0 kPa to obtain an oxide precursor, whose general chemical formula is Ni 0.6 Co 0.1 Mn 0.3 O x (The content deviation of each element is within ±1%).
[0223] Comparative Example 3
[0224] The difference from Example 2 is that:
[0225] (2) The positive electrode material hydroxide precursor is heated to 600°C at a heating rate of 2°C / min and annealed for 6 hours to obtain an oxide precursor with a general chemical formula of Ni0.67 Co 0.05 Mn 0.28 O x (The content deviation of each element is within ±1%).
[0226] Comparative Example 4
[0227] The difference from Example 1 is:
[0228] (3) The oxide precursor is mixed with Li2CO3 at a Li / Me (Me is the sum of Ni, Co, and Mn) molar ratio of 1.02:1, and ZrO2 is added with a mass content of 2000 ppm relative to the oxide precursor. The mixture is placed in an atmosphere electric heating furnace or a Joule heat reactor, using an oxygen atmosphere and a reaction pressure controlled at 10 Pa. The temperature is raised from room temperature to 900°C at a heating rate of 20°C / min, and the mixture is kept at this temperature for 12 hours. The sintered product is cooled to room temperature to obtain a matrix material.
[0229] Comparative Example 5
[0230] The difference from Example 1 is:
[0231] (3) The oxide precursor is mixed with Li2CO3 at a Li / Me (Me is the sum of Ni, Co, and Mn) molar ratio of 1.02:1, and ZrO2 is added with a mass content of 2000 ppm relative to the oxide precursor, and placed in an atmosphere electric heating furnace, using an oxygen atmosphere, and the reaction gas pressure is controlled at 10 Pa; the temperature is increased from room temperature to 700°C at a heating rate of 2°C / min, and the temperature is kept for 8 hours; the sintered product is cooled to room temperature to obtain a matrix material.
[0232] The positive electrode materials prepared in the examples and comparative examples were subjected to relevant tests, and the test data are shown in Table 1 and Table 2:
[0233] Table 1 Performance comparison of positive electrode materials of the embodiment and the comparative example
[0234]
[0235]
[0236] Table 2 Comparison of electrochemical performance of positive electrode materials of the embodiment and the comparative example
[0237]
[0238] According to the test data of Examples 1 to 11, by controlling the mass content of free nitrate ions in the positive electrode material to be between 10ppm and 100ppm, and controlling the proportion of particles with a particle size of less than 1μm in the positive electrode material to be between 8% and 16%, with the synergistic effect of an appropriate amount of free nitrate ions and particles with a particle size of less than 1μm, the high voltage resistance and high capacity of the positive electrode material can be improved, while the lithium ion transmission efficiency of the positive electrode material can be improved, and the cycle stability of the positive electrode material can be improved.
[0239] According to the test data of Example 1 and Examples 3-4, the cycle stability of the positive electrode material prepared in Example 3 is better than that of Example 1 and Example 4. The mass content of free nitrate in the positive electrode material of Example 4 is low, and the cycle stability of the positive electrode material is slightly reduced. The inventor speculates that this is because the free nitrate of the positive electrode material can induce active lithium ions to generate an appropriate amount of lithium oxide on the surface of the positive electrode material during the cycle, thereby reducing the surface energy of the positive electrode material and helping to improve the crystal structure stability of the positive electrode material.
[0240] According to the test data of Examples 4 to 8, as the mass proportion of nickel atoms in the positive electrode material increases, the discharge specific capacity of the positive electrode material also increases. As long as the mass content of free nitrate ions in the positive electrode material and the number of particles with a particle size less than 1 μm are controlled within a suitable range, different series of positive electrode materials can have high voltage resistance, high capacity and excellent cycle stability.
[0241] According to the test data of Example 2 and Example 9 and Example 1 and Example 10, since the proportion of particles with a particle size of less than 1 μm in the positive electrode material prepared in Example 9 increased compared with Example 2, although the compaction density of the positive electrode material increased, the side reactions also increased due to the increase in the number of tiny particles, so the discharge capacity and cycle capacity retention rate of the positive electrode material decreased slightly. Compared with Example 1, the proportion of particles with a particle size of less than 1 μm in the positive electrode material prepared in Example 10 decreased, and the discharge capacity and cycle capacity retention rate of the positive electrode material also increased.
[0242] According to the test data of Comparative Example 1 and Example 1, Comparative Example 2 and Example 5, Comparative Example 3 and Example 2, Figure 2 and Figure 3As shown, after the first charge and discharge of the battery prepared from the positive electrode material, the free nitrate content of the positive electrode material of Comparative Example 1 is 0. In the spectrum obtained by XPS characterization, the main component of the solid electrolyte film on the surface of the positive electrode material is ROCO2Li. The positive electrode material of Example 1 has an appropriate amount of free nitrate. After the first charge and discharge, Li2O is induced to form on the surface of the positive electrode material. Li2O has high voltage resistance, which helps to improve the high voltage resistance of the positive electrode material and reduce the side reactions between the positive electrode material and the electrolyte. Therefore, the first efficiency of the positive electrode material of Comparative Example 1 decreases, and the cycle capacity retention rate under high pressure also decreases significantly. Similarly, the discharge specific capacity, first efficiency and cycle capacity retention rate of the positive electrode material are also significantly reduced in Comparative Example 2 compared to Example 5, and in Comparative Example 3 compared to Example 2.
[0243] According to the test data of Comparative Example 4 and Example 1, the free nitrate content of the positive electrode material of Comparative Example 4 is within an appropriate range. Since the primary sintering temperature is relatively high and the heating rate is too fast, some particles are melted, and the number of particles with a particle size of less than 1 μm in the positive electrode material of Comparative Example 4 is too small, the transmission path of lithium ions increases, the compaction density of the positive electrode material decreases, the lithium ion transmission path increases, the lithium deintercalation efficiency of the positive electrode material decreases, and the discharge capacity of the positive electrode material is significantly reduced.
[0244] According to the test data of Comparative Example 5 and Example 1, the free nitrate content of the positive electrode material of Comparative Example 5 is within an appropriate range. Since the primary sintering temperature is relatively low, the number of particles with a particle size less than 1 μm in the positive electrode material of Comparative Example 5 accounts for too large a proportion, the particle size distribution width of the positive electrode material increases, the specific surface area of the positive electrode material increases, the side reaction between small particles and the electrolyte becomes more serious, and the cycle capacity retention rate of the positive electrode material decreases.
[0245] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A positive electrode material, characterized in that: The mass content of free nitrate ions in the positive electrode material is Q ppm, 10≤Q≤100; the number of particles with a particle size less than 1 μm in the positive electrode material accounts for R%, 8≤R≤16.
2. The positive electrode material according to claim 1, characterized in that It meets at least one of the following technical features: (1) The volume particle size distribution of the positive electrode material satisfies: 0.2 μm ≤ D10 ≤ 2.0 μm, 2.0 μm ≤ D50 ≤ 5.0 μm, 6.0 μm ≤ D90 ≤ 12.0 μm; (2) The volume particle size distribution of the positive electrode material satisfies: 0.8≤(D90-D10) / D50≤2.
0.
3. The positive electrode material according to claim 1, characterized in that The mass content of free sulfate in the positive electrode material is K ppm, 10≤K≤800.
4. The positive electrode material according to claim 1, characterized in that The positive electrode material is a single crystal material, and the positive electrode material includes grains with the same orientation, and the grain size of the grains is 1 μm to 5 μm.
5. The positive electrode material according to claim 1, characterized in that The chemical formula of the positive electrode material is Li n Ni x Co y N z M s O2, wherein 0.9≤n≤1.1, 0<x<1, 0<y<1, 0<z<1, 0≤s<1, x+y+z+s=1, N includes at least one of Mn and Al, and M includes at least one of Zr, Mg, W, Mo, Ti, Ba, Sr, Cr, Zn, Y, V, Cu, B, and Nb.
6. The positive electrode material according to any one of claims 1 to 5, characterized in that The specific surface area of the positive electrode material is 0.5 m 2 / g~1.5m 2 / g.
7. The positive electrode material according to any one of claims 1 to 5, characterized in that During the first cycle of charge and discharge, the structural recovery degree δ of the positive electrode material satisfies: 99.7%≤δ≤100.0%; wherein δ=θ1 / θ2*100%, θ1 is the diffraction angle of the positive electrode material at the (003) crystal plane diffraction peak measured by X-ray diffraction at the beginning of the first cycle of charging, and θ2 is the diffraction angle of the positive electrode material at the (003) crystal plane diffraction peak measured by X-ray diffraction at the end of the first cycle of discharge.
8. The positive electrode material according to any one of claims 1 to 5, characterized in that It meets at least one of the following technical features: (1) The compaction density of the positive electrode material is 2.5 g / cm 3 ~3.5g / cm 3 ; (2) The bulk density of the positive electrode material is 0.5 g / cm 3 ~1.5g / cm 3 ; (3) The tap density of the positive electrode material is 1.0 g / cm 3 ~3.0g / cm 3 .
9. A method for preparing a positive electrode material, characterized in that: The following steps are involved: The hydroxide precursor of the positive electrode material is subjected to nitration annealing to obtain an oxide precursor containing nitrate ions; A mixture of an oxide precursor containing nitrate ions and a lithium source is subjected to a sintering treatment, and the sintering product is crushed to obtain a positive electrode material, wherein the mass content of free nitrate in the positive electrode material is Q ppm, 10≤Q≤100; the number of particles with a particle size less than 1 μm in the positive electrode material accounts for R%, 8≤R≤16.
10. A battery, characterized in that: The battery comprises the positive electrode material according to any one of claims 1 to 8 or the positive electrode material prepared by the method for preparing the positive electrode material according to claim 9.
Citation Information
Cited By
Positive electrode material, positive electrode sheet and battery
EP4819235A1
Positive electrode material, positive electrode sheet and battery
WO2026103952A1